Volatility and regional growth in Europe: Does space matter? - Vicente Rios Ibá\~nez; Roberto Ezcurra (European Regional Science Association (ERSA), 2013)
This paper investigates the relationship between volatility and economic growth in the European regions over the period 1995-2008. To that end, we estimate a two way fixed effects panel data model using spatial econometric techniques that allow us to incorporate into the analysis the relevance of spatial effects in the processes of regional growth in Europe. The results show the existence of a positive and statistically signicant relationship between the fluctuations of the business cycle and regional growth, which is mainly consequence of the spatial spillovers induced by the incidence of volatility in neighbouring regions. This finding is robust to the inclusion in the analysis of different explanatory variables that may affect regional growth such as the initial GDP per capita, the level of investment or industry mix. Furthermore, the results of the paper do not depend on the specific measure of volatility used, or the spatial weights matrix employed to capture the degree of spatial interdependence between the sample regions. The observed relationship suggests that traditional stabilization policies that attempt to reduce the fluctuations of the business cycle may be harmful for economic growth in the European regions.
Keywords: 330; Volatility; growth; spatial effects; regions; Europe